STRATEGI PEMASARAN NASI BORAN : PENDEKATAN ANALISIS SWOT - Megawati Megawati; Ika Purwanti; Muhammad David; Ardiansyah Ahsanul Hayat (Kampus Akademik Publiser, 2023)
The development of the MSME sector has an important meaning in driving economic growth and reducing poverty in the country. One of the SMEs in Lamongan is Nasi Boran. Nasi Boran is a traditional food that has become Micro, Small and Medium Enterprises (MSMEs) which has become a hereditary business for the people of Lamongan, especially those from Kaotan Village, Sumberjo, Lamongan. The purpose of this study was to analyze the internal and external conditions of the rice marketing strategy implementation in Lamongan. The research method used is a qualitative descriptive (explorative) method. The sampling method was carried out by means of a non-probability sampling technique with purposive sampling and using data collection techniques by means of interviews, observations, and literature studies. The object of this study was about marketing strategy while the subject itself was the MSME perpetrators of boran rice traders in Lamongan. The data used is secondary data provided by the company, then primary data obtained from various sources of literature and journals. The analytical method used is the SWOT analysis approach. Based on the results of the research that has been described, it can be interpreted that the analysis of marketing strategy based on SWOT analysis is to obtain 2 sources of results, namely internal environmental analysis and external environmental analysis. After analyzing the marketing strategy using SWOT analysis, Nasi Boran UMKM can find out which strategy should be evaluated